Charting a new course for feminist psychology - Collins, Lynn H.; Dunlap, Michelle R., 1965-; Chrisler, Joan C. (Westport, Conn. : Praeger, 2002)
Feminist psychology is vigorous, creative, and increasingly activist. This volume reflects women's diversity and incorporates strategies for social action and opportunities for political activism. It anticipates trends and developments in the psychology of women and feminist psychology. Chapters include those about women and self-esteem, leadership skills, welfare reform, spirituality, and domestic violence. The emphasis on social activism is unique. Unusual and cutting-edge research methodologies and techniques are also discussed.
Gendered subjects in psychology: satirical and dialectic perspectives / Maureen C. McHugh, Lisa Cosgrove -- Deconstructing difference: conceptualizing feminist research from within the postmodern / Lisa Cosgrove, Maureen C. McHugh -- The faces of feminist pedagogy: a survey of psychologists and their students / Merideth J. Tomlinson, Ruth E. Fassinger -- Women of color and feminist psychology: moving from criticism and critique to integration and application / Michelle K. Williams, Terry McCandies, Michelle R. Dunlap -- Deconstructing attachment theory: naturalizing the politics of motherhood / Susan H. Franzblau -- Dimensions of silencing and resistance in adolescent girls: development of a narrative method for research and prevention / Joseph Spinazzola, Helen W. Wilson, Vicki B. Stocking -- Self-esteem inoculation: protecting girls from the effects of sexism / Lynn H. Collins -- Women, whither goest thou? To chart new courses in religiousness and spirituality and to define ourselves! / Carole A. Rayburn, Lee J. Richmond -- HIV among elderly women: ignored and overlooked by health care providers and public policy makers / Jennifer M. Hillman, Kristin J. Broderick -- Black battered women: new directions for research and Black feminist theory / Carolyn M. West -- Hormone hostages: the cultural legacy of PMS as a legal defense / Joan C. Chrisler -- Prevention of eating disorders: problems, pitfalls, and feminist possibilities / Lori M. Irving -- Body image disturbance and disordered eating in African-American and Latina women / Eleanor F. Gil-Kashiwabara -- Stories of violence: use of testimony in a support group for Latin American battered women / Marja Booker -- "We all need different kinds of help": poor women's perspectives on welfare reform / Ingrid Johnston-Robledo, Renee N. Saris -- Women, federal policy, and social change: bringing a feminist presence to Capitol Hill / Jeanine C. Cogan, Camille Preston.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
English.
digitized
Keywords: Feminist psychology; Feminism; Women -- Psychology; Women -- psychology; Feminism; Psychologie féministe.; Féminisme.; Femmes -- Psychologie; feminism; PSYCHOLOGY -- Reference; Feminism; Feminist psychology; Women -- Psychology; Feministische psychologie; Vrouwen; Meisjes; Cognitieve psychologie; Paradigma's.; Feminismus; Psychologie; Aufsatzsammlung; Feminism; Women's movement; Women; Womyn